The influence of family function and resilience to self-efficacy and self-esteem mediating by family role in breast cancer patients: A PLS-SEM - Rosliana Dewi; Johan Budhiana; Hana Haryani; Fera Melinda (Jurnal Keperawatan Padjadjaran, 2026)
Background: Breast cancer is known as one of the most dangerous types of cancer in the world. Managing self-efficacy and self-esteem in breast cancer patients presents a major challenge. Purpose: This study aims to analyze the influence of family function and family resilience on self-efficacy and self-esteem in breast cancer patients by positioning family role as a mediator variable in a structural model based on the Family Centered Empowerment Model. Methods: This study used a cross-sectional design. The population consists of breast cancer patients, with a sample size of 102 respondents using total sampling. The independent variables are family functioning and resilience, while the dependent variables are self-efficacy and self-esteem, with family role as the intervening variable. The inferential analysis used was Structural Equation Modelling Partial Least Squares by evaluating the measurement model (outer model), evaluating the structural model (inner model), and testing hypotheses. Results: Family function and family resilience significantly predicted family role (p = 0.007) and (p = 0.012), respectively. Family role, in turn, significantly predicted self-efficacy (p < 0.001) and self-esteem (p < 0.001). The model explained 30.8% of the variance in family role, 52.6% in self-efficacy, and 29.2% in self-esteem. Conclusions: Family function and family resilience significantly influence family role, which subsequently predicts self-efficacy and self-esteem among breast cancer patients. Longitudinal studies are warranted to further clarify causal pathways and validate the stability of this structural model.